Nodular vasculitis or erythema induratum without cutaneous tuberculosis: An unusual presentation in an uncommon site - Ramin Mofarrah; Nafiseh Jallab; Ramina Mofarrah; Kousar Jahani Amiri; Naghmeh Jallab (Our Dermatology Online, 2021)
Erythema induratum (EI) is a rare chronic disease, which occurs with cutaneous tuberculosis (TB). Nodular vasculitis, much rarer than erythema induratum, describes the same condition but without cutaneous TB, with lesions usually in the lower legs and rarely on the breasts. We report the case of a 46-year-old female with a history of crusted skin and necrotic lesions two years before, which, once self-limited, multiplied one month before and transferred to uncommon sites of the body, such as the breast. There was no evidence of other clinical presentations, and a chest X-ray gave no pathological findings. A biopsy was taken from the lesions, and the patient was diagnosed with erythema induratum without cutaneous tuberculosis, that is, nodular vasculitis. After treatment with calcineurin-inhibiting tacrolimus ointment, topical corticosteroids, and immunosuppressive oral azathioprine, the lesions improved.